Functionalized Organic–Inorganic Liposome Nanocomposites for the Effective Photo-Thermal Therapy of Breast Cancer - Liu, Haibin; Zhuang, Feng; Zhang, Chengjian; Ai, Wanzhao; Liu, Wei; Zhou, Xukun (Frontiers in Materials, 2021)
Organic-inorganic nanocomposites for photothermal therapy of cancers has emerged as a promising strategy against malignant tumors. However, it is still a big challenge to develop a nanocomposite system that can maximize the synergistic photothermal therapy effect as well as preserve high stability for simultaneous delivery of the chemotherapeutic drugs and photothermal agents. Here, we have exploited a organic liposome containing inorganic core for co-loading the aggregates of bovine serum albumin(BSA), indocyanine green (ICG), and doxorubicin (DOX), abbreviated as BID-liposomal nanocomposites. The three kinds of abstances were aggregated in the core of liposomal nanocomposites through hydrophobic and electrostatic interactions. In vitro characterization shows that BID-liposomal nanocomposites were spherical nanoparticles with size of 30-50 nm and good storage stability. Moreover, BID-liposomal nanocomposites illustrates the most strongest cytotoxicity among all the formulations against murine 4T1 tumor cells. In breast cancer-bearing mouse models, BID-Liposomes lead to significant improvements in tumor inhibition effects with no obvious toxicity. Therefore, the BID-liposomal nanoparticle is believed to be a promising strategy for chemo-photothermal therapy against cancers.